Harmony Search-Based Hyper-Heuristic For Scheduling Problems - Anwar, Khairul (2018)
Scheduling problems are encountered in every field which are typically related to services such as in hospital, transportation, and also educational institutions. These problems can be extremely difficult when its involves a large number of events or resources to be scheduled and a wide variety of constraints which need to be satisfied or taken into consideration. Hence, many heuristic and meta-heuristic approaches have been introduced to solve these problems. However, some institutions look for a method that can deal with a wide range of scheduling problems without spending a lot of money and times as long the solutions produced are acceptable.